An Investigation to Understand the Need for Financing Small and Medium Enterprise in ‎Afghanistan (Salam International Academic Journal, 2020)
Small business firms are important and integral part of any economy. They generate employment ‎and income when they do business and tend to expand. With fast growing globalization trends, ‎new opportunities and threats for small business are opening. But there are some perceived and ‎actual threats for survival of micro and small firms. These include cutthroat competition, ‎aggressive marketing, reach to credit and global linkage with foreign firms. Largely the small and ‎micro scale units are concentrated in all over Afghanistan. The units located hear complete for the ‎share of the local market for different type of business. Hence, there is a sort of cluster in this ‎geographical area which is important for employment generation as well.‎
Keywords: Financing; Enterprise; Investigation; Afghanistan; Capital invested